Properties and Applications of a New Extended Gamma Function Involving Confluent Hypergeometric Function - Abdus Saboor; Gauhar Rahman; Hazrat Ali; Kottakkaran Sooppy Nisar; Thabet Abdeljawad (Journal of Mathematics)
In this paper, a new confluent hypergeometric gamma function and an associated confluent hypergeometric Pochhammer symbol are introduced. We discuss some properties, for instance, their different integral representations, derivative formulas, and generating function relations. Different special cases are also considered.